2018
DOI: 10.1021/acsanm.7b00324
|View full text |Cite
|
Sign up to set email alerts
|

Folic-Acid-Functionalized Graphene Oxide Nanocarrier: Synthetic Approaches, Characterization, Drug Delivery Study, and Antitumor Screening

Abstract: In this work, we developed and screened the potential antitumor activity of a nanocarrier based on graphene oxide (GO) and folic acid (FA) for the delivery of chemotherapy drugs. GO was synthesized by the graphite exfoliation process. FA was linked to PEG (4,7,10-trioxa-1,13-tridecanediamine) to form FA–PEG, followed by coupling to the GO surface. Camptothecin (CPT) was further adsorbed on GO for use as a drug model in the delivery study. The synthesis of the intermediate FA–PEG molecule and coupling to GO for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 72 publications
3
50
0
1
Order By: Relevance
“…Thus, the present study corroborates the discussions regarding CPT release experiments and is in agreement with the data in the literature. 34 The above discussion clearly shows the differences in the nanocomposite based on graphene oxide decorated with silica nanoparticles as a nanocarrier; this material has optimized drug delivery characteristics compared with those of MSN and GO materials. These properties suggest the potential application of GO-MSN nanomaterials as nanocarriers in antitumor treatment.…”
Section: Cpt Release Studies From the Msn + Cpt Go + Cpt And Go-msn mentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, the present study corroborates the discussions regarding CPT release experiments and is in agreement with the data in the literature. 34 The above discussion clearly shows the differences in the nanocomposite based on graphene oxide decorated with silica nanoparticles as a nanocarrier; this material has optimized drug delivery characteristics compared with those of MSN and GO materials. These properties suggest the potential application of GO-MSN nanomaterials as nanocarriers in antitumor treatment.…”
Section: Cpt Release Studies From the Msn + Cpt Go + Cpt And Go-msn mentioning
confidence: 93%
“…Studies related to GO materials comprising CPT as a drug host molecule are still rare and show promising results from the point of view of high encapsulation capacity. 34,35 However, the literature has reported toxic effects of GO, such as cell membrane damage and a high capacity to cause haemolysis, 30,36 thus increasing the chance of toxicity in intravenous applications. There are also studies that show opposite effects, characterized by a low haemolytic effect.…”
Section: Introductionmentioning
confidence: 99%
“…The high affinity of the folate receptor that is preferentially expressed in cancer cells is rarely expressed in normal cells. This has allowed the development of the targeted delivery of anticancer drugs at the cancer at the tumor sites to maximize anticancer efficacy with minimizing side effects to healthy tissues [ 42 , 43 , 44 , 45 ]. The folate targeting of cancerous cells has been reported recently in many studies; e.g., L. Xing et al 2018 used folate targeting for ovary cancer cells, and found that folate receptor alpha (FRα) is overexpressed in ovary cancer cells [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nano-sized GO (nGO) was functionalized by amino terminal branched PEG initially in 2008 by the connecting amino and carboxyl. 12 In addition to PEG, other amineterminated biomaterials such as chitosan (CS), 13 carboxymethyl CS, 14 galactosylated CS, 15 polyethylenimine (PEI), 16 poly(allylamine hydrochloride) (PAH), 17 dextran (DEX), 18 folic acid (FA) 19 and aptamer 20 can be covalently linked to GO by amidation reaction. Despite the lack of amino, hyaluronic acid (HA) can also be grafted to GO…”
Section: Covalent Modi¯cationmentioning
confidence: 99%